Sustainable tourism development strategy: Integration of environmental, social, and economic sustainability in business and economic research - Manggaprouw, Ramayana Edilio; Wurarah, Rully Novie; Mustiah, Djumiati (Journal of Economic, Business & Accounting Research, 2025)
Background: Tourism development in Kabui Bay, Raja Ampat, faces unique challenges in integrating local economic interests with environmental and social sustainability. Methods: This study evaluates the tourism potential in Kabui Bay by focusing on implementing ecotourism principles and local community participation. The study identified key factors that influence sustainable tourism development through a qualitative methodology that included in-depth interviews, field observations, and document analyses. Findigns: The results showed that although Kabui Bay has excellent potential as an ecotourism destination, there is an urgent need for sustainable infrastructure development, capacity building of local communities, and effective marketing strategies to attract tourists. Conclusion: The research recommends closer cooperation between government stakeholders, the private sector, and local communities to ensure that tourism development brings equitable economic benefits while maintaining the cultural values and natural wealth of Kabui Bay. Novelty/Origanality of this article: This study uniquely highlights the integration of ecotourism principles with local community participation in Kabui Bay, emphasizing the need for sustainable infrastructure and strategic collaboration for balanced tourism development.